2016
DOI: 10.3109/10826084.2015.1117107
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Nutrition-Related Behaviors in Alcohol-Dependent Patients After Outpatient Detoxification: The Role of Chocolate

Abstract: In the first month after outpatient alcohol detoxification treatment, significant changes in nutrition-related behaviors were observed. These changes were not associated with alcohol craving. For a subgroup, increasing the frequency of chocolate consumption might be a temporary protective factor with respect to alcohol relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 29 publications
2
11
1
Order By: Relevance
“…For example, a study examining the macronutrient composition of dietary intake in 64 newly sober alcoholic patients found significantly escalated sugar and carbohydrate intake in those who stayed sober longer [36]. Similar alterations in the nutrition-related behavior were also recently reported by a study in which abstainers in an outpatient alcohol detoxification program consumed 3 times more chocolate compared to nonabstainers [37]. While these data may demonstrate a protective effect of excessive intake of palatable food on alcohol consumptions, it is unclear if sugar decreased alcohol drinking or alcohol withdrawal increased sugar consumption triggered by a coping mechanism or gateway drug effect.…”
Section: Human Studiessupporting
confidence: 59%
See 1 more Smart Citation
“…For example, a study examining the macronutrient composition of dietary intake in 64 newly sober alcoholic patients found significantly escalated sugar and carbohydrate intake in those who stayed sober longer [36]. Similar alterations in the nutrition-related behavior were also recently reported by a study in which abstainers in an outpatient alcohol detoxification program consumed 3 times more chocolate compared to nonabstainers [37]. While these data may demonstrate a protective effect of excessive intake of palatable food on alcohol consumptions, it is unclear if sugar decreased alcohol drinking or alcohol withdrawal increased sugar consumption triggered by a coping mechanism or gateway drug effect.…”
Section: Human Studiessupporting
confidence: 59%
“…Since neuroendocrine peptides that regulate energy metabolism can also influence emotional states and reinforcing properties of alcohol [23], a compromised nutritional status may further exacerbate various behavioral impairments observed in alcoholics and could substantially contribute to this chronic relapsing disorder [94,96]. Importantly, increased intake of highly palatable food has been documented in human alcoholics during recovery [36,37], suggesting that palatable food consumption might be protective during the early stages of alcohol detoxification process to maintain sobriety. On a similar note, the propensity to consume highly palatable food could compete with the propensity of alcohol drinking, as shown in a large sample of adolescent girls further supports this idea [97].…”
Section: Future Directionsmentioning
confidence: 99%
“…For example, it is unclear if a diet high in fat is necessary to trigger reduced alcohol drinking behavior or if a diet high in sugar would induce the same effect. While a recent study showed a reduction of alcohol withdrawal syndrome following a high fat/ketogenic diet intake [62], studies exist demonstrating that excessive consumption of palatable/sweet food could curb alcohol drinking behavior in human alcoholics [10,11] which also agrees with the Alcoholics Anonymous recommendation of eating more sweet/palatable food to reduce alcohol craving [63]. These data collectively suggest that palatable food may compete with propensity to drink alcohol as both are capable of interacting with the brain reward circuitry.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, alcoholics have lower body weight and reduced body mass index compared to healthy controls, which signify a poor nutritional status [7,8], a condition that could contribute to AUD pathology [7,9]. Interestingly, alcoholics display an increased intake of highly palatable food during recovery [10,11]. However, it is unclear if this is an attempt to restore caloric deficits or to alleviate the negative consequences of alcohol withdrawal.…”
Section: Introductionmentioning
confidence: 99%
“…Both study subgroups noted a change in appetite when entering recovery, transitioning from barely eating, to eating frequently due to increased hunger or boredom. This aligns with previous studies on this population [36,[38][39][40][41] in which processed, quick, and sweet foods are commonly consumed when entering recovery. There are several potential reasons for the relationship seen between dietary habits and substance use.…”
Section: Chapter Iv: Discussionsupporting
confidence: 90%